Dissolution and Solubility Product of Cd-Fluorapatite [Cd5(PO4)3F] at pH of 2–9 and 25–45°C. (30th August 2018) - Lin, Ju; Zhu, Zongqiang; Zhu, Yinian; Liu, Huili; Zhang, Lihao; Jiang, Zhangnan
Abstract : Dissolution of the synthetic cadmium fluorapatite [Cd5 (PO4 )3 F] at 25°C, 35°C, and 45°C was experimentally examined in HNO3 solution, pure water, and NaOH solution. The characterization results confirmed that the cadmium fluorapatite nanorods used in the experiments showed no obvious variation after dissolution. During the dissolution of Cd5 (PO4 )3 F in HNO3 solution (pH = 2) at 25°C, the fluoride, phosphate, and cadmium ions were rapidly released from solid to solution, and their aqueous concentrations had reached the highest values after dissolution for <1 h, 1440 h, and 2880 h, respectively. After that, the total dissolution rates declined slowly though the solution Cd/P molar ratios increased incessantly from 1.55∼1.67 to 3.18∼3.22. The solubility product for Cd5 (PO4 )3 F (K sp ) was determined to be 10 −60.03 (10 −59.74 ∼10 −60.46 ) at 25°C, 10 −60.38 (10 −60.32 ∼10 −60.48 ) at 35°C, and 10 −60.45 (10 −60.33 ∼10 −60.63 ) at 45°C. Based on thelog   K sp values obtained at an initial pH of 2 and 25°C, the Gibbs free energy of formation for Cd5 (PO4 )3 F (Δ G f 0 ) was calculated to be −4065.76 kJ/mol (−4064.11∼−4068.23 kJ/mol). The thermodynamic parameters for the dissolution process were computed to be 342515.78 J/K·mol, −85088.80 J/mol, −1434.91 J/K·mol, and 2339.50 J/K·mol forΔ G 0, Δ H 0, Δ S 0, andΔ C p 0, correspondingly.